2019
DOI: 10.1002/jat.3934
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different bisphenol derivatives on oxidative stress, DNA damage and DNA repair in RWPE‐1 cells: A comparative study

Abstract: Bisphenol A (BPA) is a well-known endocrine disruptor and it is widely used mainly in the plastics industry. Due to recent reports on its possible impact on health (particularly on the male reproductive system), bisphenol F (BPF) and bisphenol S (BPS) are now being used as alternatives. In this study, RWPE-1 cells were used as a model to compare cytotoxicity, oxidative stress-causing potential and genotoxicity of these chemicals. In addition, the effects of the bisphenol derivatives were assessed on DNA repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 73 publications
4
23
0
Order By: Relevance
“…GSH levels in this study were observed to be increase in the hepatocytes with concentrations that ranged between 15.63 and 250 µM; however, a signi cant decrease in the GSH content was determined with 500 µM of BPF. Similar to the results herein, Kose et al reported elevated GSH levels in RWPE-1 cells that were treated with BPA, as well as its analogues, BPF and BPS, for 24 h [16]. In another study, Maćczak et al [15] found depleted GSH levels in human erythrocytes exposed to BPF.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…GSH levels in this study were observed to be increase in the hepatocytes with concentrations that ranged between 15.63 and 250 µM; however, a signi cant decrease in the GSH content was determined with 500 µM of BPF. Similar to the results herein, Kose et al reported elevated GSH levels in RWPE-1 cells that were treated with BPA, as well as its analogues, BPF and BPS, for 24 h [16]. In another study, Maćczak et al [15] found depleted GSH levels in human erythrocytes exposed to BPF.…”
Section: Discussionsupporting
confidence: 86%
“…For example, cytotoxicity was increased on a dosedependent basis in human cell lines (HCLs), such as hepatoma HCL, HepG2; intestinal HCL, LS174T; and renal HCL, ACHN, treated with BPF concentrations ranging from 5 to 100 µM for 24 h [24]. Similarly, BPFinduced cytotoxicity was reported with concentrations of 0-600 µM for 24 h in RWPE-1 cells [16]. Russo et al reported that mouse embryo broblast cells and cancer cells exposed to BPF (0-300 µM for 48 h) resulted in increased cytotoxicity in a dose-dependent manner [25].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This genotoxic effect could be due to the potential of BPS to induce oxidative stress both in vivo ( 96 , 97 ) and in vitro ( 98 , 99 ). A modified version of the Comet assay demonstrated that BPS induced a genotoxic effect in human prostatic cells and that such effects were strictly associated to oxidative stress mechanisms ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely that BPS has the potential to interfere with, and disrupt the normal functions of endocrine system in organisms ( 51 ). Moreover, the genotoxic potential of BPS is also cause of concern since scientific literature reports conflicting results depending on the investigated experimental model ( 52 , 53 ). As the usage of BPS as a substitute to BPA is increasing there is an urgent need to improve our knowledge about possible adverse effects of BPS on physiological functions in living organisms.…”
Section: Introductionmentioning
confidence: 99%